19th Prof. Vladas Gronskas International Scientific Conference. Reviewed Selected Papers - Šarkiūnaitė, Ingrida (Vilnius University Proceedings, 2025)
In keeping with the scholarly traditions of Vilnius University Kaunas Faculty, the 19th “Prof. Vladas Gronskas International Scientific Conference” was held in November 2024. This international conference is an arena for cooperation and scholarly fellowship, with young researchers, bachelor, master, and doctoral students from Lithuania as well as Latvia, Turkey, Bulgaria, participating in the different conference sections. The main goal of this scientific gathering has always been to contribute to a reliable, safe, effective, and sustainable economy and business development. Thus, the organizing committee strives to create a suitable platform for well‐grounded and open discussion where young researchers have the opportunity to present and share their insights. Encouraging entrepreneurship is a crucial condition for economic growth, and this puts forward a new approach to business, creativity, value creation, and the implementation of innovations. It is precisely in this context that business and science should interact. To reinforce this relevant bond, the guest speakers of the plenary session were selected amongst scientists and experienced practitioners – Prof. Vlado Dimovski (Distinguished expert in management and organizational theory at the University of Ljubljana, Faculty of Economics, Slovenia), Stepas Telešius (Co-founder, shareholder and board member of ACME Grupė and Chairman of the Board of “Vesta Consulting”, a sustainable business consultancy, Lithuania), Edgaras Abromavičius (Head of esports and games of the Lithuanian Football Federation, working on projects together with UEFA, FIFA and other international organizations, Lithuania). This conference encourages internationalization and closer cooperation between science and business. Hopefully, there has been some useful takeaway for both academia and business conference participants: new insights and inspirations for further scientific research.